Description of Student Characters in Science Learning - Faif Pasani, Chairil; Yulinda, Ratna (International Journal of Psychosocial Rehabilitation, 2020)
Character education is a deliberate effort to help individuals understand and conduct ethical values. The character of personality-forming learners can be formed through science learning. Learners gain knowledge by understanding natural phenomena, and as an impact, they can develop various characters in life skills. The purpose of this research is to describe the student’s character through science learning. This research is a quasi-experiment with a time-series design. Based on the results, it could be concluded that students’ characters tend to change from “starting to appear” to “starting to develop” criteria. Based on the results obtained, so as to grow the character of curiosity in science learning, then teachers need to design learning by including the character of curiosity in the learning process.